Utility of Bone Marrow Examination in a Secondary Care Hospital - Saqib Qayyum Ahmad,Obaid Ullah Khan, Nadeem Zafar (Journal of Rawalpindi Medical College, 2011)
Background: To analyze utilization of bone marrow examination in a secondary health care hospital. Methods: In this observational study bone marrow examination and interpretation was done in the light of patients’ clinical history and relevant laboratory investigations. Patients were followed up to see any complications due to bone marrow aspiration and trephine procedures. Results: Pancytopenia (29.8%) and unexplained anaemias (28.6%) were the commonest indications. Anaemias due to nutritional deficiencies (42.8%) and haematological malignancies (29.7%) were the commonest diagnosis. No complications were seen in any of the patients. Conclusions:Nutritional deficiencies were the commonest diagnosis, even though they can be prevented